2019
DOI: 10.1038/s41386-019-0583-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic link between right prefrontal cortical activity and anxious arousal revealed using transcranial magnetic stimulation in healthy subjects

Abstract: Much of the mechanistic research on anxiety focuses on subcortical structures such as the amygdala; however, less is known about the distributed cortical circuit that also contributes to anxiety expression. One way to learn about this circuit is to probe candidate regions using transcranial magnetic stimulation (TMS). In this study, we tested the involvement of the dorsolateral prefrontal cortex (dlPFC), in anxiety expression using 10 Hz repetitive TMS (rTMS). In a within-subject, crossover experiment, the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…However, this distinction is not universal [71][72][73] . Consistent with this laterality effect, we recently measured fear-and anxiety-potentiated startle before and after 10 Hz stimulation to the right dlPFC, and found that 10 Hz stimulation increased anxiety-potentiated startle, suggesting that the right dlPFC may be important for anxiety expression rather than regulation 17 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, this distinction is not universal [71][72][73] . Consistent with this laterality effect, we recently measured fear-and anxiety-potentiated startle before and after 10 Hz stimulation to the right dlPFC, and found that 10 Hz stimulation increased anxiety-potentiated startle, suggesting that the right dlPFC may be important for anxiety expression rather than regulation 17 .…”
Section: Discussionmentioning
confidence: 57%
“…Sample size was based on our previous study exploring the effect of right dlPFC rTMS on anxiety, which used a similar design 17 . Twenty-five participants were enrolled in the study.…”
Section: Participantsmentioning
confidence: 99%
“…Similarly, healthy subjects show elevated right dlPFC activity during complex cognitive tasks performed under threat of shock ( Oei et al , 2012 ; Balderston et al , 2017b 2017c ). However, this argument is inconsistent with neuromodulatory data targeting the right dlPFC, showing that excitatory repetitive transcranial magnetic stimulation (rTMS) increases anxiety ( Balderston et al , 2020 ) while inhibitory rTMS reduces anxiety ( Chen et al , 2013 ). In addition, retention interval activity is often left-lateralized, especially when verbal stimuli are used ( Altamura et al , 2010 ; Rottschy et al , 2012 ), making the functional significance of these anxiety-related right dlPFC changes unclear.…”
Section: Introductionmentioning
confidence: 90%
“…One critical region thought to be important for WM manipulation is the dorsolateral prefrontal cortex (dlPFC) ( Balderston et al , 2016b ). Using threat of shock to induce anxiety is one approach to studying the relationship between anxiety and cognition ( Robinson et al , 2013 ; Grillon et al , 2019 ); however, additional research is needed to determine whether this approach can shed light on the cognitive symptoms seen in anxious patients and inform the identification of treatment targets for anxiety disorders ( Balderston et al , 2020 ). Therefore, the purpose of this study is to examine the WM-related dlPFC activity in anxiety patients and controls and to examine whether this activity is affected by manipulations in anxiety state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we set out to gather a large dataset of existing trait anxiety scores from labs across multiple institutions who routinely collect trait anxiety measures in their behavioural and MRI studies 1,25,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] . In order to control for possible confounds and examine interaction effects, we additionally collected the following variables: gender, age, whether and how participants were screened for affective/psychiatric disorders, and whether the study involved the presence of a stressor and/or pharmacological manipulation (see Methods for details).…”
Section: Introductionmentioning
confidence: 99%